Lectures on complex networks - q (Oxford : Oxford University Press, 2010)
This text is an introduction to the science of complex networks which fills the gap between popular science books and comprehensive reference volumes on complex networks. It discusses the main directions of modern research in this active field, as well as the history of network studies.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Computer networks; Information networks; System analysis; Mathematical physics